Wireless Sensor Network Based Gas Monitoring System Utilizing ZigBee Technology - Coboi, Alberto; Nguyen, Minh T.; La, Kien T.; Vu, Thang C. (Journal of Electronics and Electrical Engineering, 2023)
This paper presents a ZigBee-based wireless network gas monitoring system, utilizing ZigBee technology to enable reliable and low-cost communication. The system leverages small sensor nodes and ZigBee protocols to collect data on physical phenomena, particularly gas levels, in various environments. The network’s low-power consumption and extended range capabilities allow for effective gas sensing within a radius of up to 300 meters. While interoperability with devices from different manufacturers remains a limitation, the system showcases the versatility of ZigBee technology in diverse fields. The study evaluates the system’s performance through simulation and experimentation, addresses potential challenges, and proposes future developments to enhance ZigBee-based wireless network gas monitoring systems, offering improved remote monitoring and manipulation capabilities. Furthermore, our research contributes to the advancement of wireless sensor network technology by demonstrating the practicality of ZigBee in gas monitoring. The findings from our experiments and simulations provide valuable insights into the optimization of such systems, which can have far-reaching impacts on environmental monitoring, safety, and industrial processes. In addition, our proposed enhancements pave the way for more reliable and efficient remote monitoring and control, offering substantial benefits for various industries, including environmental management, industrial automation, and beyond.